Synthesis of novel thiourea-/urea-benzimidazole derivatives as anticancer agents - Siddig Lamia A. (De Gruyter, 2021)
A new series of urea and thiourea derivatives containing benzimidazole group as potential anticancer agents have been designed and synthesized. The structures of the synthesized compounds were characterized and confirmed by spectroscopic techniques such as 1H NMR, 13C NMR, and mass spectrometry. In vitro anticancer assay against two breast cancer (BC) cell lines, MDA-MB-231ER(−)/PR(−) and MCF-7ER(+)/PR(+), revealed that the cytotoxicity of 1-(2-(1H-benzo[d]imidazol-2-ylamino)ethyl)-3-p-tolylthiourea (7b) and 4-(1H-benzo[d]imidazol-2-yl)-N-(3-chlorophenyl)piperazine-1-carboxamide (5d) were higher in MCF-7 with IC50 values of 25.8 and 48.3 µM, respectively, as compared with MDA-MB-231 cells. Furthermore, 7b and 5d were assessed for their apoptotic potential using 4′,6-diamidino-2-phenylindole, acridine orange/ethidium bromide staining, and Caspase-3/7. After incubation with MCF-7, the compounds 7b and 5d induced apoptosis through caspase-3/7 activation. In conclusion, the compounds 7b and 5d are potential candidates for inducing apoptosis in different genotypic BC cell lines.